Petrologic characterization and tectonic implications of blueschist and greenschist facies rocks of Jambaló, Cauca (2017)
Jambaló greenschist and blueschist are found in a metamorphic unit that belongs to the Arquía complex. Metamorphism of these rocks is associated with the subduction of the Proto-Caribbean under the South American plate. Age of metamorphism has been estimated by Bustamante (2008) with Ar-Ar method as Maastrichtian-Danian (67-61 Ma). Paragenesis of blueschist facies rocks is Glaucophane (Fe-glaucophane) + quartz + phengite + albite + epidote + chlorite (pycnochlorite) garnet, and paragenesis of greenschist facies rock is albite + quartz + chlorite (pycnochlorite) + calcite + epidote. Greenschist rocks have been altered by an infiltrating fluid with CO2, transforming the paragenesis from a paragenesis with actinolite to a paragenesis with calcite and with absence of actinolite. Protholits of theses rocks were obtained through mineral chemistry, whole rock composition and paragenesis analysis, defining a metapelitic protholit for blueschist rocks and a metabasic protholit for greenschist rocks. According to P-T conditions, both rock types reached approximately the metamorphic peak at 9.2 kbar and 481°C, which corresponds to the transitional assemblage between greenschist to blueschist facies. Petrography provides evidence of retrogression with a slight overprint of a lower facies (greenschist). However, rocks preserve their peak assemblage, indicating a hairpin retrograde path. According to this path and to lithologic relations between the studied rocks, it was suggested an exhumation of serpentinite-subduction channel type